Early postoperative acute myocardial infarction in kidney transplant recipients: A nested case‐control study. Issue 5 (23rd March 2021) - Deeb, Maya; Gupta, Nikita; Overgaard, Christopher B.; Li, Yanhong; Famure, Olusegun; Joseph Kim, S.
Abstract: Introduction: The epidemiology of early acute myocardial infarctions after kidney transplantation has not been well characterized. This study sought to examine the incidence, risk factors, and clinical outcomes of early acute myocardial infarctions or EAMI in kidney transplant recipients. Methods: A total of 1976 patients who underwent kidney transplantation at our center from Jan 1, 2000, to Sept 30, 2016, were included. A nested case‐control design was used to study EAMI risk factors using a conditional logistic regression model. A Cox proportional hazards model was used to assess the association of EAMI with death‐censored graft failure, death with graft function, and total graft failure. Results: Seventy four patients had an EAMI within 3 months post‐transplant. Based on univariable analyses, risk factors for EAMI included age and recipient history of diabetes mellitus or coronary artery disease. After adjustment, recipient history of coronary artery disease was the only independent predictor for EAMI (OR 3.76, p  < .001). Patients who experienced EAMI were more likely to experience death‐censored graft failure, death with graft function, and total graft failure. Conclusion: While the incidence of EAMI in kidney transplant recipients is relatively low, these data show that EAMI has profound long‐term effects on morbidity and mortality.